Liquidity And Leverage's Impact On Profitability From 2018 To 2022 - Mismiwati Mismiwati; Arifia Nurriqli; Nurlia Nurlia; Winda Lestari (International Journal of Economics and Management Research, 2023)
The purpose of this study is to determine the effect of liquidity and leverage on profitability in Mining Companies in the Coal Mining Sub Sector which are listed on the Indonesia Stock Exchange for the 2018-2022 period. The researcher obtained 93 populations consisting of 18 companies which were used as a sample using the company's financial statements as secondary data. And using panel data regression analysis so that the results obtained are that Liquidity and Leverage simultaneously affect Profitability in mining companies in the coal mining sub-sector for the 2018-2022 period. Liquidity has a negative and insignificant effect on profitability. Whereas,